2012
DOI: 10.1186/1754-6834-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a synthetic mixture composed of major Trichoderma reesei enzymes for the hydrolysis of steam-exploded wheat straw

Abstract: BackgroundAn efficient hydrolysis of lignocellulosic substrates to soluble sugars for biofuel production necessitates the interplay and synergistic interaction of multiple enzymes. An optimized enzyme mixture is crucial for reduced cost of the enzymatic hydrolysis step in a bioethanol production process and its composition will depend on the substrate and type of pretreatment used. In the present study, an experimental design was used to determine the optimal composition of a Trichoderma reesei enzyme mixture,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…[12,13] Previous work has also shown that cellulase synergism is more apparent during the hydrolysis of more crystalline cellulosic substrates, with little or no synergy observed on amorphous cellulose (e.g., phosphoric acid swollen cellulose (PASC)). [20][21][22][23][24][25][26] We [27] and other workers [28,29] have shown that the pretreatment and nature of the cellulosic substrate used resulted in significant variations in substrate characteristics, such as cellulose accessibility, degree of polymerization (DP), and crystallinity. [11,15,16] These sometimes contradictory observations indicate that the relationship between enzyme synergism and the nature of the cellulosic substrate has not been fully resolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] Previous work has also shown that cellulase synergism is more apparent during the hydrolysis of more crystalline cellulosic substrates, with little or no synergy observed on amorphous cellulose (e.g., phosphoric acid swollen cellulose (PASC)). [20][21][22][23][24][25][26] We [27] and other workers [28,29] have shown that the pretreatment and nature of the cellulosic substrate used resulted in significant variations in substrate characteristics, such as cellulose accessibility, degree of polymerization (DP), and crystallinity. [11,15,16] These sometimes contradictory observations indicate that the relationship between enzyme synergism and the nature of the cellulosic substrate has not been fully resolved.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] As mentioned earlier, only a limited number of studies have explored the extent of synergistic cooperation among cellulases and other enzymes during hydrolysis of pretreated lignocellulosic substrates. [20][21][22][23][24][25][26] We [27] and other workers [28,29] have shown that the pretreatment and nature of the cellulosic substrate used resulted in significant variations in substrate characteristics, such as cellulose accessibility, degree of polymerization (DP), and crystallinity. The amount and nature of the non-cellulosic components, such as residual hemicellulose; lignin; and the type of lignin-carbohydrate complexes remaining after pretreatment have also been shown to impede the effectiveness of enzymatic hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Including beta-xylosidase and xylanase in the mixture (CBH1/ CBH2/EG1/BGL/BXL/XYN) led to higher conversion of AFEX-pretreated corn stover (above 80% in 24 h) than the industrial enzyme complexes Spezyme or Accelerase (Gao et al, 2009(Gao et al, , 2011. The importance of xylanase addition was also demonstrated for steam-pretreated wheat straw although only low levels of xylan are left after this pretreatment (Billard et al, 2011). Addition of other auxiliary enzymes (β-xylosidase, α-arabinofuranosidase and α-glucuronidase) increased xylose yields, but without increasing glucose yields further.…”
Section: Improvement Of Enzyme Cocktails By Optimization Of Enzyme Ramentioning
confidence: 60%
“…EG1 levels, on the contrary, had to be increased to about 35%, compared to 5-10% in a T. reesei cocktail. Higher EG1 ratios were also necessary for optimized hydrolysis of ammonia-fiber expansion pretreated corn stover and steamexploded wheat straw (Billard et al, 2011). Including beta-xylosidase and xylanase in the mixture (CBH1/ CBH2/EG1/BGL/BXL/XYN) led to higher conversion of AFEX-pretreated corn stover (above 80% in 24 h) than the industrial enzyme complexes Spezyme or Accelerase (Gao et al, 2009(Gao et al, , 2011.…”
Section: Improvement Of Enzyme Cocktails By Optimization Of Enzyme Ramentioning
confidence: 97%
“…The incompatibility of bacterial and fungal derived enzyme mixtures with bio-feedstock cell walls results in limited access to cellulose structural targets and an inability to harvest sequestered cellulosic energy stores (Billard et al, 2012;Banerjee et al, 2010;Arantes and Saddler, 2010). Additionally, their exogenous expression produces difficulties such as die codons, codon usage mismatches, and aberrant splicing (US 2002/0062502 A1, May 23, 2002.…”
Section: Introductionmentioning
confidence: 97%